Efectiveness and safety of very low calory diets in obese patients - M. Sáez Belló; C. Segarra Villalba; E. Gras Colomer; P. Frias Ruiz; M. Climente Martí (Farmacia Hospitalaria)
Purpose: To evaluate effectiveness, safety and adherence of Very Low Calory Diet (VLCD) in patients with obesity. Methods: Observational prospective descriptive study. Patients with BMI >30 kg/m2 who started VLCD were included. We arranged 3 pharmacotherapeutical consultations, picking up the variables: age, sex, BMI, side effects and number of VLCD cycles. We defined effectiveness as weight loss in absolute and relative terms and weight loss rate (kg/week); safety as incidence and severity of side effects by the Farmacovigilance Spanish System (SEFV); and adherence by a SMAQ adapted questionnaire. Results: 29 women and 15 men were included, with a mean of 42 years. 5 patients did not complete the follow-up. Effectiveness: weight loss average was 7kg (IQR 9,5 a 5,3) and relative of 6,7%, (p < 0.0005). The weight loss rate was 1,2kg per week (IQR 1,6 a 0,9). Safety: 33% of the patients described side effects. All of them were mild (37% constipation, 16% dizziness, 12% anxiety, 5% headache, 2% gases y 2% epigastrical pain). Adherence: 84% of the patients were adherent by the SMAQ adapted questionnaire: 74% in the first cycle and 92% in the following ones. The relation between the number of cycles and the adherence did not get statistical differences (p = 0,1127). Conclusions: Effectiveness and adherence to the treatment could improve in obese patients by setting interdisciplinary measures in the daily clinical practice.